Initiatives to improve quality of education in the Kurdistan region, Iraq : administration, school monitoring, private school policies, and teacher training - Vernez, Georges (Research report (Rand Corporation), 2016)
"The Kurdistan Regional Government (KRG) aims to restructure its Ministry of Education, develop a framework and implementation plan for a school quality assurance system, review the effectiveness of its monitoring and support of private schools, and assess the content and quality of in-service teacher training. To help the KRG in their efforts, RAND researchers interviewed Ministry of Education staff and reviewed the current situation; reviewed relevant literature on organization design, school monitoring, and private schools; conducted in-depth case studies of ministries of education, school monitoring, and private schools in other countries; analyzed data on KRG teachers; provided analysis and recommendations; and developed implementation guidelines"--Publisher's description